PERCEIVED ORGANIZATIONAL SUPPORT, WORK ETHIC AND COMPENSATION ON ORGANIZATIONAL COMMITMENT - Nur Umami, Kharisma Aulia; Widhiandono, Hengky; Darmawan, Akhmad; ., Alfalisyado (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study aims to analyze the effect of perceived organizational support, work ethic and compensation on organizational commitment. The population is all employees in the outsourcing company PT Despan Berkah Abadi Cilacap Regency. The sample of this study amounted to 110 respondents with a nonprobability sampling technique with a saturated sample approach where the entire population was sampled. The analysis process involves classical assumption tests which include normality tests, multicollinearity tests and heteroscedasticity tests. Then hypothesis testing which includes the T test, coefficient of determination and multiple linear regression analysis. The results of this study are the perception of organizational support has a significant negative effect on organizational commitment. Work ethic has a significant positive effect on organizational commitment. Compensation has a significant positive effect on organizational commitment.